Investigation of micro-scale shear response of sand-rubber granule mixture in terms of particle shape and grain scale deformability effects - Ari, Abdulmuttalip; Akbulut, Suat (ELSEVIER SCIENCE INC, 2024)
In this study, the effects of particle shape of rigid sand and soft rubber materials on macro -scale shear response were reasoned based on micro -scale parameters. For this purpose, first, the shape properties of three different sand and two different rubber samples were quantified using image processing techniques, and the contact model parameters were calibrated through physical experiments. The direct shear test was simulated in a two-dimensional discrete element software with realistic particle forms. The soft nature of rubber particles was reflected using body -centered cubic packing with a linear -parallel bond contact model. As a result, coordination number, distribution of contact forces (i.e., strong contact, and fabric anisotropy), and contact sliding were derived by the numerical analyses. It has been observed that the particle shape leads to distinctive micro -scale responses due to the variations in the stiffness of the contacts. (c) 2024 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.
Keywords: Particle shape; Sand; Rubber; Shear response; Micro-scale response; Discrete element method; BEHAVIOR; DEM; SIMULATIONS; ASSEMBLIES; MACRO; STATE; Engineering; Materials Science